PROOFS OF SOME THEOREMS OF ELEMENTARY ALGEBRA BY THE METHOD OF MATHEMATICAL INDUCTION (Global Conference on Multidisciplinary Research and Innovation, 2026)
The square of a polynomial with n terms is equal to the sum of the squares of all its terms plus twice the sum of all possible pairwise products of its terms.